Effect of ultraviolet irradiation on the cross-linking process and ceramic yield of liquid hyperbranched polycarbosilane. (17th November 2017) - Ji, Peng; Pei, Xueliang; Miao, Yulong; He, Liu; Huang, Qing
ABSTRACT: Liquid hyperbranched polycarbosilanes (LHBPCSs) with different reactant molar ratios of chloropropene/chloromethyltrichlorosilane were synthesised by Grignard coupling, followed by reduction. Different from traditional thermal cross-linking for LHBPCS, ultraviolet (UV) irradiation cross-linking was used. The molecular weight and hardness of LHBPCS increased with prolonging UV irradiation time. According to Fourier transform infrared result, the –Si–H, –Si–H2 and allyl groups were consumed. Possible cross-linking reactions (hydrosilylation, allyl group polymerisation and dehydrocoupling) were discussed. The ceramic yield of LHBPCS showed an increase trend with increasing the UV irradiation time. After 1 h of UV irradiation for LHBPCS-1 (the molar ratio of chloropropene to chloromethyltrichlorosilane was 1:9), 78.0 wt-% ceramic yield was obtained. In addition, LHBPCS with higher allyl group content had fewer pores in it. By heating LHBPCS-1 cross-linked by UV irradiation to 1400°C, a non-porous SiC ceramic was obtained.